Holmes and new profiles in translation (2011)
ABSTRACT: Holmes (1972) proposed a scheme of translation studies which served as the predicting basis of the discipline, and that, with some modifications, is still valid. In Holme’s map, the discipline was divided classically into “pure” and “applied” branches, each one broken down into several subfields, which may reflect the state-of-the-art of the whole range of publications in translation. This wide array of fields and subfields would not have been possible if the profession would not have diversified in accordance with the evolution of society’s needs, which can be observed in the many profiles of the translation activity at present.